Antioxidant and Chromatographic Profile of Ganoderma lucidum - Idu, MacDonald; Okojie, Susan Omo; Gabriel, Benjamin Ogunma; Okhuoya, John A. (African Journal of Sciences and Traditional Medicine, 2024)
Ganoderma lucidum is a medicinal fungus which possesses a wide range of biological activities due to its nutritional, antioxidant and therapeutic values. This study examine the antioxidant and phytochemical properties of G. lucidum aqueous extracts in Sample A (boiled for 1 hour) and Sample B (boiled for 3 hours). The antioxidant activity and DPPH radical-scavenging assay were determined using standard procedures, while further phytochemical composition of the extracts was determined through chromatographic analysis. Sample A demonstrated higher DPPH radical scavenging activity (67.85%) while Sample B, displayed an increased trend with time compared with ascorbate. Total Antioxidant Capacity (TAC) analysis, revealed Sample A with higher TAC (56.79 mg/ml) than Sample B (51.71 mg/ml). Phytochemical composition of G. lucidum aqueous extracts exhibited higher percentage of alkaloids at Sample A (3.00 ± 0.12%) and TAC (56.79 ± 0.04 µg/ml), while Sample B displayed higher percentages of saponins (8.00 ± 0.12%), flavonoids (51.50 ± 0.77 µg/ml), proanthocyanidins (38.23 ± 0.18 µg/ml), phenols (16.18 ± 0.07 µg/ml), and FRAP (64.00 ± 2.00 mg/ml). Chromatographic profiles illustrated that both samples displayed 32 peaks, with varying constituents. The highest peak in Sample A was recorded at PEAK 22 (31.317), while in Sample B was observed at PEAK 37 (35.927). These peaks represented different identified constituents, including Pyrrolidine, 1-methyl-3, 2'-spiro-benzo-1, 3-dioxolane-Benzene, 1,3,5-tris(2,2-dimethylpropyl)-2-iodo-4-nitro-Propanamide, and 2,2-dimethyl-N-(3-methylphenyl)-. These findings provide insights into the potential health benefits associated with G. lucidum and guide further exploration of its bioactive compounds.